Long Term Evolution 4G and Beyond - Paradisi, Alberto; Yacoub, Michel Daoud; Lira Figueiredo, Fabrício; Tronco, Tania; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book focus on Long Term Evolution (LTE) and beyond. The chapters describe different aspects of research and development in LTE, LTE-Advanced (4G systems) and LTE-450 MHz such as telecommunications regulatory framework, voice over LTE, link adaptation, power control, interference mitigation mechanisms, performance evaluation for different types of antennas, cognitive mesh network, integration of LTE network and satellite, test environment, power amplifiers and so on. It is useful for researchers in the field of mobile communications.
LTE and Beyond -- Brazilian Telecommunications Regulatory Framework and the Impacts on the Development of Broadband Radio Access Systems -- Dual-Polarized Crossed Dipole Antenna Array for LTE Base Station -- Evaluation of the LTE 450 MHz system performance with different terminal antennas.-Wavelet-based Narrowband Interference Suppression in Long Term Evolution Physical Channels.
Keywords: Telecommunication; Computer networks .; Electronic circuits; Communications Engineering, Networks; Computer Communication Networks; Microwaves, RF Engineering and Optical Communications; Electronic Circuits and Systems